The field - Paul, Baptiste (NorthSouth Books, Inc., an imprint of NordSüd Verlag, 2018)
Children form teams, build a pitch, and play a joyous game of soccer, in a book with English and Creole (as spoken in Saint Lucia) vocabulary words.